The Role of Adult Education and skills Training in promoting Planned Change and Localization: The Case of ACORD-NEBBI Community Development Programme in Uganda - Paschal Odoch (Adult Education Research Conference, 2000)
The study explored the ways in which adult education and skills training programs can contribute to the achievement of equitable, self-reliant, and sustainable community development. Using a case study design, the research investigated the factors that support or hinder the ability of adult education programs to achieving equitable, self-reliant, and sustainable communities.